Migration of tritium in the components of the natural environment - Pushkarov, Oleksandr; Sevruk, Iryna; Shramenko, Ivan; Zubko, Oleksandr; Viter, Volodymyr (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Formulation of the problem. Tritium formed as a result of natural or man-made processes is included in migration flows depending on the forms of its presence – gaseous (NT), aqueous (NTO) and organically bound (OZT). According to these forms, tritium is redistributed among various components of the natural environment and distributed in the environment according to the laws of the hydrogen cycle in nature.Materials and methods. During atmospheric transport, the tritium concentration decreases according to the laws of diffusion in air plumes. Part of tritium with atmospheric precipitation falls on the surface of water bodies, where it is diluted to background concentrations, on vegetation and soil. The further geochemical history of these precipitations is determined by the laws of biogeochemical and hydrogeochemical migration and inclusion in the short-term and long-term cycles in the biosphere.Results. According to the results of monitoring the content of tritium in the snow cover and in atmospheric moisture in the zone of influence of radioactive waste preservation (SFRW) projects, it was determined that the formation of atmogeochemical anomalies of tritium depends on the constructive features of the confinement, geomorphological and landscape-geochemical factors (relief forms, type and structure of the forest ecosystem) , the presence of technological premises, which play the role of natural and man-made barriers in the way of the movement of air masses, as well as from the wind rose generalized for the control period. Biogeochemical migration of tritium occurs with water from atmospheric precipitation in the soil-plant system. Tritium, like a hydrogen isotope, participates in all processes of biogeomigration, which is primarily determined by the biological role of water and organic matter. The main biophysical processes determining the biogeomigration of tritium include: initial deposition on the surface of the soil and vegetation, conversion of tritiated hydrogen (HT) into tritiated water (HTO) in the soil due to bacterial oxidation, absorption of HTO by plants with the conversion of a part of HTO into an organically bound form (OZT), transportation of HTO in soil and absorption of HTO by roots, re-emission of HTO into the atmosphere from soil and plants. Hydrogeochemical migration of tritium in surface reservoirs and watercourses causes its dilution to background concentrations. Yes, in discharges from the nuclear power plants of Ukraine in Dnipro (Kakhovsky Reservoir), Horyn, Styr, P. Bug on the weekend, downstream of the tritium concentrations exceed 20÷50 Bq×dm–3.Conclusions. According to the results of radio-hydrogeological monitoring of the territories adjacent to the SFRW, the main factors influencing the formation of tritium hydrogeofiltration flows in the geological environment were determined. These include: the intensity of the release of tritiated water from RAW storage facilities, hydraulic permeability, hydrophysical parameters and the mineral composition of the zone of unsaturated filtration, the topography of the surface of the water-resistant horizon and seasonal fluctuations in the amount of atmospheric precipitation to the local aquifer. The long-term operation of tritium hydrogeofiltration flows in the system "aeration zone (ZA) – underground aquifer (SAW)" causes their spread to a distance that significantly exceeds the planned dimensions of the containers and the territory of the SFRW.